2022
DOI: 10.1093/ehjci/jeab289.039
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial reservoir strain may be a load independent index of diastolic dysfunction in liver cirrhosis patients

Abstract: Funding Acknowledgements Type of funding sources: None. Introduction Cirrhotic cardiomyopathy is characterized by high cardiac output, reduced peripheral resistance and diastolic dysfunction. Specifically, diastolic dysfunction has been correlated with the prognosis in liver cirrhotis patients independently of the disease severity. Left atrial reservoir strain (LASr) is a novel index which is inversely correlated with left ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…They also reported a trend toward reduced post-transplant survival in patients with a reduced LA reservoir and conduit strain [44]. Dimitroglou et al did not find a significant association between LA reservoir strain and MELD score but found an association with the E/e' ratio, indicating an association of LA strain with DD [68]. Similarly, Meucci et al reported that patients with advanced DD grade had worse values of LA strain and, interestingly, worse prognosis.…”
Section: Speckle Tracking Echocardiography For the Evaluation Of Left...mentioning
confidence: 97%
“…They also reported a trend toward reduced post-transplant survival in patients with a reduced LA reservoir and conduit strain [44]. Dimitroglou et al did not find a significant association between LA reservoir strain and MELD score but found an association with the E/e' ratio, indicating an association of LA strain with DD [68]. Similarly, Meucci et al reported that patients with advanced DD grade had worse values of LA strain and, interestingly, worse prognosis.…”
Section: Speckle Tracking Echocardiography For the Evaluation Of Left...mentioning
confidence: 97%